Effect of organic linker substituent on catalytic activity of UiO-66 metal-organic framework in selective oxidation of propylene glycol: homolytic versus heterolytic activation of hydrogen peroxide. (June 2022) - Torbina, V.; Ten, S.; Vodyankina, O.
Abstract: A family of isoreticular metal-organic frameworks, based on the UiO-66 structure with NH2 -, OH-, HSO3 -, and NO2 -substituted terephthalic acid, are synthesized and tested as catalysts in liquid-phase oxidation of propylene glycol (PG) with hydrogen peroxide and compared with the catalytic performances of unsubstituted UiO-66. The obtained materials are characterized by X-ray diffraction, FT-IR, thermogravimetric analysis (TGA), nuclear magnetic resonance spectroscopy ( 1 H NMR), and Fourier-transform infrared spectroscopy (FT-IR) of adsorbed CO and scanning electron microscopy (SEM) methods. Hydroxyacetone (HA) is the main product over all X-UiO-66 catalysts under the reaction conditions used. The nature of substituent drastically affects the PG conversion and the oxidant utilization efficiency. The presence of electron-withdrawing groups in the organic linker leads to preferential heterotic activation of H2 O2, whereas the increase of electron density around Zr active sites, promoted by electron-donating groups, enhances the unproductive homolytic oxidant decomposition. The insertion of NO2 group results in almost double increase in the HA yield (15.5 vs. 8.8%) and hydrogen peroxide utilization efficiency (98 vs. 36%) in comparison with the reaction catalyzed by H-UiO-66. The NO2 -UiO-66 can be recycled without the loss of the catalytic activity and preserves its structure after the catalytic cycle. Highlights: Substituent in linker structure plays a key role in activity of the H-UiO-66 catalyst. Control of the electron density on Zr sites affects the H2 O2 activation mechanism. NO2 -UiO-66 features a double increase in propylene glycol conversion at high hydroxyacetone selectivity. NO2 -UiO-66 can be recycled without loss of catalytic activity in propylene glycol oxidation.